Pemahamam dan Praktik Petani dalam Penggunaan Bahan Aktif Zinc Fosfit dan Brodifakum untuk Mengatasi Hama Tikus di Desa Tembok Bahalang Kecamatan Hulu Sungai Tengah Kabupaten Barabai - Muhammad, Fadhel; Hidayah, Aulia Azizatul; Lestari, Jayniah Trisna Ayu; Arba'i, Hasan; Nadia, Dwi; Alfisyah, Alfisyah; Azkia, Fatimah (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
In an effort to effectively control rat pest populations, farmers have begun considering the use of active ingredients such as Zinc Phosphide and Brodifacoum, which are known to be effective in reducing pest impact. Farmers were provided with understanding and practical training on the use of Zinc Phosphide and Brodifacoum as part of a more systematic and targeted pest control strategy. This study aims to explore farmers’ understanding and practices in applying Zinc Phosphide and Brodifacoum, as well as to identify the challenges they face in implementation. The research method employed is the Participatory Action Research (PAR) approach, which emphasizes the active involvement of farmers as key partners in every stage of the research. In addition, the Asset-Based Community Development (ABCD) approach was used to explore the potential resources available within the community. The findings show that this research was conducted to identify farmers’ knowledge and practices related to the use of these two active ingredients. Furthermore, farmers also gained an understanding of the use of Brodifacoum as an active ingredient for controlling rat pests.